PEWARISAN GEN SAPI KEMBAR: PELUANG PENINGKATAN POPULASI DI INDONESIA / The Inheritance of Twinning Gene in Cattle: Option for Population Improvemnet in Indonesia - Bess Tiesnamurti (Jurnal Penelitian dan Pengembangan Pertanian, 2019)
The evidence of cattle with twinning birth is reported over the world, as well as in Indonesia, with the frequency in dairy cattle is a bit higher compared to beef cattle (4ƒ{10% : 1%). The heritability of twinning cattle is considered to be low, so does for the repeatability. This paper outlines the inheritance of twin born cattle, its geographic distribution and utilization for population accelaration as well as its contribution for meat supply. In Indonesia, twin born cattles are reported in 11 provinces and occured in Ongole crossbred (PO), Bali, Angus, Aceh, SimmentalxPO crossbred, LimousinexPO crossbred and FH breeds. The occurence of cattle with twinning birth in dairy and beef cattle is around 27.250 and 165.990 heads, with estimation 13.625 and 82.995 heads of dairy and beef cows, respectively. The optimistic scenario is expected to deliver 19.735 and 71.406 heads of dairy and beef calves every year, whereas pesimistic scenario resulting the birth of dairy and beef calves of 10.306 and 50.875 heads, respectively. These scenarios contribute to 2,6% and 1,8% of national calves born (3.500.000 heads every year) for optimistic and pesimistic scenarios, respectively, indicating that twinning genes in cattle do not significantly contribute to the addition of calves born in Indonesia. Several efforts to maintain the the population of twin born cattle can be conducted through option such as a) to maintain the twin born cattle population to the institution belongs to government or private; b) to allow farmers to raise the twin born cattle and c) to empower local farmers association as a networking who raise the twin born cattle. Eventhough the twin born calves contribution is low for national calves born, however, it is suggested to keep the genetic values for further requirement in the future, to provide technologies for early identification or moleculer of twinning cattle carriers as well as to explore the genetic potential for further development. In the future, development of the twinning cattle can be conducted through frozen sperm distribution for artificial insemination.Keywords: Beef cattle, dairy cattle, gene for twinning, heritability AbstrakSapi dengan potensi beranak kembar memiliki frekuensi kelahiran lebih tinggi pada sapi perah (410%) dibanding sapi potong (1%). Laju pewarisan (heritabilitas) sifat kelahiran kembar sangat rendah, demikian pula dengan laju pengulangan (ripitabilitas). Tulisan ini membahas sifat pewarisan gen sapi beranak kembar di Indonesia, distribusi sapi dengan potensi gen kelahiran kembar, peluang pemanfaatannya bagi peningkatan populasi dan penyediaan daging sapi. Di Indonesia, kelahiran kembar sapi terdapat di 11 provinsi dan terjadi pada rumpun sapi PO, Aceh, Bali, FH, persilangan Aberden Angus, persilangan Simmental x PO, persilangan Limousine x PO. Gen beranak kembar sapi perah dan sapi potong berturut turut diperkirakan sekitar 27.250 ekor dan 165.990 ekor, dimana populasi sapi betina sekitar 13.625 dan 82.995 ekor untuk sapi perah dan sapi potong. Skenario optimis pemanfaatan gen sapi kembar , diharapkan dapat memberikan angka kelahiran sebanyak 19.735 dan 71.406 ekor, berturut-turut untuk sapi perah dan sapi potong. Sementara skenario pesimis menghasilkan kelahiran anak sapi perah dan sapi potong, berturut-turut sejumlah 10.306 dan 50.875 ekor. Kedua skenario tersebut menyumbang 2,6% (optimis) dan 1,8 % (pesimis) dari total kelahiran per tahun (3.500.000 ekor). Keberadaan sapi beranak kembar di Indonesia belum memberikan sumbangan nyata bagi peningkatan populasi, akan tetapi perlu dipertahankan keberadaannya. Berbagai usulan yang dapat dilakukan untuk mempertahankan populasinya antara lain: a) pengumpulan di satu tempat, baik milik pemerintah atau swasta yang tertarik memelihara dan melakukan pengamatan dengan biaya yang sangat mahal; b) pemeliharaan sapi kembar diserahkan kepada peternak dengan konsekuensi sewaktu waktu akan punah karena keterbatasan kemampuan membiayai pemeliharaan, c) membentuk kelompok peternak pemelihara sapi kembar sebagai sarana pertukaran informasi. Namun demikian, eksplorasi sifat genetik perlu terus dilakukan baik secara konvensional maupun secara molekuler, sementara pengembangan sapi kembar dapat dilakukan melalui pembuatan semen beku yang diimplementasikan dengan teknologi inseminasi buatan.Kata Kunci: Sapi potong, sapi perah, gen beranak kembar, heritability.